2016
DOI: 10.1158/0008-5472.can-16-0530
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: PHGDH Expression Is Required for Mitochondrial Redox Homeostasis, Breast Cancer Stem Cell Maintenance, and Lung Metastasis

Abstract: Intratumoral hypoxia stimulates enrichment of breast cancer stem cells (BCSC), which are critical for metastasis and patient mortality. Here we report a metabolic adaptation that is required for hypoxia-induced BCSC enrichment and metastasis. Hypoxiainducible factors coordinately regulate expression of genes encoding phosphoglycerate dehydrogenase (PHGDH) and five downstream enzymes in the serine synthesis pathway and mitochondrial one-carbon (folate) cycle. RNAi-mediated silencing of PHGDH expression in both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
225
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(242 citation statements)
references
References 52 publications
16
225
1
Order By: Relevance
“…In breast cancer cells, PHGDH knockdown and consequent impairment of the mitochondrial folate cycle led to a decrease in NADPH level of ~50 and ~30% in MDA-MB-231 and in MCF7 cell lines, respectively (107), thus confirming the prediction by Fan and colleagues. Interestingly, exposure of breast cancer cell lines to hypoxia led to a repressed expression of G6PD, while increasing the expression of genes involved in serine synthesis pathway and mitochondrial folate cycle (107). These data suggest that HIF-1α is involved in the switch from cytosolic to mitochondrial NADPH production by upregulating the mitochondrial folate cycle.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In breast cancer cells, PHGDH knockdown and consequent impairment of the mitochondrial folate cycle led to a decrease in NADPH level of ~50 and ~30% in MDA-MB-231 and in MCF7 cell lines, respectively (107), thus confirming the prediction by Fan and colleagues. Interestingly, exposure of breast cancer cell lines to hypoxia led to a repressed expression of G6PD, while increasing the expression of genes involved in serine synthesis pathway and mitochondrial folate cycle (107). These data suggest that HIF-1α is involved in the switch from cytosolic to mitochondrial NADPH production by upregulating the mitochondrial folate cycle.…”
Section: Discussionsupporting
confidence: 79%
“…Hypoxia upregulates PHGDH, PSAT1, PSPH, SHMT2, MTHFD2, and MTHFD1L, thus protecting breast cancer stem cells from oxidative damage (107). Consistent with this notion, PHGDH knockdown abrogates breast cancer stem cell survival under hypoxia, without impairing cancer cell proliferation, and increases oxygen consumption rate and extracellular acidification rate as a consequence of reduced glucose shunting to the serine synthesis pathway.…”
Section: Mitochondrial Folate Cycle and Serine Pathwaymentioning
confidence: 99%
“…More recently, it was found that increased expression of the serine synthesis enzyme phosphoglycerate dehydrogenase (PHGDH) in some cancers can result from copy number gain of a region on chromosome 1p (Beroukhim et al, 2010; Locasale et al, 2011; Possemato et al, 2011) or a consequence of oncogenic signaling, including NRF2 and ATF4 signaling (DeNicola et al, 2015), or hypoxia responses (Samanta et al, 2016). The PHGDH gene encodes the enzyme that catalyzes conversion of the glycolytic intermediate 3-phosphoglycerate into 3-phosphohydroxypyruvate, and 3-phosphohydroxypyruvate is converted to serine via two subsequent reactions (Figure 6).…”
Section: Altered Metabolic Enzyme Expressionmentioning
confidence: 99%
“…In breast cancer cells, analysis of gene expression revealed that, irrespective of the estrogen receptor (ER) status, hypoxia induced the expression of the three enzymes of the SSP (PHGDH, PSAT1 and PSPH) and three enzymes required for mitochondrial 1CM (SHMT2, MTHFD2, and MTHFD1L) in a HIF-dependent manner [34]. In contrast, the enzymes required for cytosolic 1CM (SHMT1, MTHFD1) were not hypoxia-induced in most breast cancer cell lines.…”
Section: Hif Regulates Antioxidant Defenses In Hypoxic Cellsmentioning
confidence: 99%